SESAM Mode-Locked Yb:Ca3Gd2(BO3)4 Femtosecond Laser - Huang-Jun Zeng; Zhang-Lang Lin; Wen-Ze Xue; Ge Zhang; Zhongben Pan; Haifeng Lin; Pavel Loiko; Xavier Mateos; Valentin Petrov; Li Wang; Weidong Chen (Applied Sciences, 2021)
We report on the first passively mode-locked femtosecond-laser operation of a disordered Yb:Ca3Gd2(BO3)4 crystal using a SEmiconductor Saturable Absorber Mirror (SESAM). Pumping with a single-transverse mode fiber-coupled laser diode at 976 nm, nearly Fourier-transform-limited pulses as short as 96 fs are generated at 1045 nm with an average output power of 205 mW and a pulse repetition rate of ~67.3 MHz. In the continuous-wave regime, high slope efficiency up to 59.2% and low laser thresholds down to 25 mW are obtained. Continuous wavelength tuning between 1006–1074 nm (a tuning range of 68 nm) is demonstrated. Yb:Ca3Gd2(BO3)4 crystals are promising for the development of ultrafast lasers at ~1 μm.